Analisis Efisiensi Filter Bacterial Universal Dengan Port Adapter Pada Ventilator GE Carescape R860 Menggunakan Metode Uncertainty - Dian Bambang Pramusinto; Sri Arttini Dwi Prasetyowati (LPPM POLBITRADA, 2026)
The frequency of filter replacement that must always be replaced increases the hospital's budget requirements for consumables (BHP). An alternative solution is to replace the original filter with a universal filter with the addition of ports so that it can be compatible on the ventilator machine. This study aims to analyze the effect of using universal bacterial filters modified with ports to be compatible with ventilators. The research was conducted with a quantitative approach and internal and external calibration methods according to SNI IEC 62353: 2014 and ISO 80601-2 standards. The parameters tested included tidal volume, minute volume, breath rate, inspiratory-expiratory ratio (I:E), peak inspiratory pressure (PIP), mean airway pressure (MAP), positive end-expiratory pressure (PEEP), inspiratory time (Ti), and fraction of inspired oxygen (FiO₂). Uncertainty analysis was used to assess the feasibility of the measurement results. The results showed that the use of a universal filter with added ports kept the ventilator performance within the set tolerance limits and was technically feasible. In addition, this solution was able to significantly reduce the cost of filter procurement compared to the original filter.